2011
DOI: 10.1016/j.yqres.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Barrier island response to late Holocene climate events, North Carolina, USA

Abstract: The Outer Banks barrier islands of North Carolina, USA, contain a geologic record of inlet activity that extends from ca. 2200 cal yr BP to the present, and can be used as a proxy for storm activity. Optically stimulated luminescence (OSL) dating (26 samples) of inlet-fill and flood tide delta deposits, recognized in cores and geophysical data, provides the basis for understanding the chronology of storm impacts and comparison to other paleoclimate proxy data. OSL ages of historical inlet fill compare favorabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…Between 1846 and 2008, the shoreline retreated landward by 70 m at a long-term rate of 0.43 m/y (Maio et al, 2014). The destabilization of barrier systems in response to accelerated rates of sea level rise coupled with high-energy storm events has been observed along coastal barriers along the U.S. East Coast and the Gulf of Mexico (Ashton, Donnelly, and Evans, 2008;Mallinson et al, 2011;Seminack and Buynevich, 2001). Numerous studies have shown that coastal barriers are rapidly migrating landward and degrading (FitzGerald, Buynevich, and Rosen, 2001;FitzGerald et al, 2007;Khalil, Finkl, and Raynie, 2013;Mallinson et al, 2010;Williams, Penland, and Sallenger, 1992).…”
Section: Rapid Coastal Change Along South Cape Beach Characteristic Omentioning
confidence: 99%
See 2 more Smart Citations
“…Between 1846 and 2008, the shoreline retreated landward by 70 m at a long-term rate of 0.43 m/y (Maio et al, 2014). The destabilization of barrier systems in response to accelerated rates of sea level rise coupled with high-energy storm events has been observed along coastal barriers along the U.S. East Coast and the Gulf of Mexico (Ashton, Donnelly, and Evans, 2008;Mallinson et al, 2011;Seminack and Buynevich, 2001). Numerous studies have shown that coastal barriers are rapidly migrating landward and degrading (FitzGerald, Buynevich, and Rosen, 2001;FitzGerald et al, 2007;Khalil, Finkl, and Raynie, 2013;Mallinson et al, 2010;Williams, Penland, and Sallenger, 1992).…”
Section: Rapid Coastal Change Along South Cape Beach Characteristic Omentioning
confidence: 99%
“…Storm-driven barrier breaching and the formation of new inlets can lead to dramatic perturbations in adjacent coastal landforms and ecosystems (Buynevich and FitzGerald, 2003;Mallinson et al, 2011). These include a potential rapid increase in wave and tidal energy within back-barrier settings, the salinization of freshwater environments, alterations to important marine transportation routes, and the destruction of coastal infrastructure (Buynevich and FitzGerald, 2003;FitzGerald, van Heteren, and Montello, 1994;Maio et al, 2014;Mallinson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two quartz sanddominated samples were sent to Utah State University Luminescence Laboratory for OSL analysis using the single aliquot regenerative (SAR) method. Preparation followed the general procedures outlined in Mallinson et al (2011). OSL ages are converted to cal yr BP by subtracting 62 years (samples were analyzed in 2012).…”
Section: F Age Analysismentioning
confidence: 99%
“…This reflects the historically documented closures of many inlets in the Outer Banks (Figure 1). Mallinson et al (2011) suggested that inlet closure could be related to fewer storm impacts during the past 300 years. New Currituck Inlet closed around 200 years ago (Stick, 1958;Fisher, 1962) almost completely closing off Currituck Sound from any marine influence.…”
Section: < 500 (Modern Scenario)mentioning
confidence: 99%